A Critical Survey on: Cloud Security and privacy issues and its associated solutions - Sharma, Smita; RP, Singh (International Journal of Computer Sciences and Engineering, 2019)
Cloud computing is a set of web-based resources and services. Cloud services are delivered worldwide from data centers. By providing virtual resources via the internet, cloud computing facilitates its consumers. Google apps, provided by Google and Microsoft SharePoint, are a general example of cloud services. The rapid growth in the "cloud computing" field also increases serious security concerns. Security remained a constant problem for Open Systems and the Internet. Lack of security is the only obstacle to broad cloud computing adoption. The cloud computing boom has created many security challenges for consumers and service providers. This survey aims to identify the most vulnerable security threats in cloud computing, enabling both end users and vendors to understand the key security threats associated with cloud computing. Our work will enable researchers and security professionals to know about the concerns of users and vendors and critical analysis of the various proposed security models and tools. In a cloud computing environment, all data resides over a set of networked resources, enabling access to data via virtual machines. Because these data centers may be beyond the reach and control of users in any corner of the world, there are multiple security and privacy challenges that need to be understood and addressed. There are various issues that need to be addressed in a cloud computing scenario regarding security and privacy. This survey paper aims at elaborating and analyzing the numerous unresolved issues that threaten the adoption and diffusion of cloud computing.